2015
DOI: 10.1093/hmg/ddv013
|View full text |Cite
|
Sign up to set email alerts
|

Maternal gestational diabetes is associated with genome-wide DNA methylation variation in placenta and cord blood of exposed offspring

Abstract: Exposure of a developing foetus to maternal gestational diabetes (GDM) has been shown to programme future risk of diabetes and obesity. Epigenetic variation in foetal tissue may have a mechanistic role in metabolic disease programming through interaction of the pregnancy environment with gene function. We aimed to identify genome-wide DNA methylation variation in cord blood and placenta from offspring born to mothers with and without GDM. Pregnant women of South Asian origin were studied and foetal tissues sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
144
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(156 citation statements)
references
References 39 publications
8
144
1
3
Order By: Relevance
“…The prevalence of GDM has been estimated at ~7% of pregnancies in the USA [1]. Gestational diabetes affects both the mother and the offspring.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of GDM has been estimated at ~7% of pregnancies in the USA [1]. Gestational diabetes affects both the mother and the offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Finer et al found that maternal gestational diabetes leads to genome-wide DNA methylation difference in the placenta and cord blood of exposed offspring. Pathways involved in MAPK signaling are enhanced in methylation genes [40]. Nyggf4 , which is a newly discovered obesity candidate gene, may regulate the methylation levels of various isoforms of the MAPK subfamily [41].…”
Section: Discussionmentioning
confidence: 99%
“…The study reported a similar methylation pattern for MEST in a group of obese adults compared to that in normal-weight controls. A study on placenta tissue from 27 GDM and 21 healthy pregnancies (67) found 1708 differentially methylated positions (>5%) that reached significance (P < 0.05) after FDR. Pathways that were differently methylated included endocytosis, mitogen-activated protein kinases (MAPK) signaling pathway, cell adhesion molecules (CAMs), focal adhesion, chemokine signaling and insulin signaling pathways.…”
Section: Other Genesmentioning
confidence: 99%